Pathogenetic mechanisms of macular holes: a review of recent research work - R. R. Fayzrakhmanov; O. A. Pavlovsky; G. O. Karpov (Российский офтальмологический журнал, 2023)
The literature review focuses on penetrating macular holes, a topical issue in vitreoretinal surgery. Multiple theories and the modern view on the pathogenetic mechanisms macular hole formation are presented. A classification of macular holes is proposed.